FACING DIFFICULTIES WITH GAMES IN TEFL FOR YOUNG LEARNERS AND MINIMIZING THESE CHALLENGES - Gafforova, Sevara (Educational Research in Universal Sciences, 2023)
The purpose of this paper is to study further problems that teachers and younger students may face during playing games in English as a foreign language classes and finding some relevant solutions to these challenges. This study was designed as a mixed-method study. A total of 12 teachers from different parts of Uzbekistan and 12 students of grade 6B of Chust Specialized Boarding School N:7 participated in this study. An online and offline questionnaire and a video were used as the data collection. The data obtained from the questionnaires were analyzed using content analysis. The result of the study demonstrated that teachers should deal with problems such as failure to control of the class and reduction in students’ motivation whereas students may lose their interest to other activities and argue with each other during playing games. Although playing games are a good method to use in the class, above problems should find their solutions in order to make games rather more effective.